Pengaruh Metode Token Economy dalam Meningkatkan Kepatuhan Siswa Disabilitas Intelektual Ringan - Anggraeni, Safrina Devi; Yaum, Lailil Aflahkul; Mais, Asrorul (JOEAI (Journal of Education and Instruction), 2025)
This study aimed to determine the effect of implementing the token economy method on improving compliance among students with mild intellectual disabilities at the Arya Satya Hati Special Needs School (SLB). This study used a Single Subject Research (SSR) method with an A–B design consisting of a baseline phase (5 sessions) and an intervention phase (5 sessions). The results showed an increase in compliance from an average of 37% in the baseline phase to 77% in the intervention phase. The conclusion is that implementing the token economy method is efficacious in improving compliance among students with mild intellectual disabilities, making it a viable alternative behavioral intervention strategy in SLB. These findings also provide practical implications for SLB teachers in utilizing the token economy as a behavior development strategy.   Keywords: Mild Intellectual Disability, Token Economy